2020
DOI: 10.31979/mti.2020.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Effective Metropolitan Areawide Public Transit: A Comparison of European, Canadian, and Australian Case Studies

Abstract: (Caltrans), and by private grants and donations. MTI's transportation policy work is centered on three primary responsibilities: MINETA TRANSPORTATION INSTITUTE LEAD UNIVERSITY OF Mineta Consortium for Transportation Mobility Research MTI works to provide policy-oriented research for all levels of government and the p rivate sector to foster the development of optimum surface transportation systems. Research areas include: bicycle and pedestrian issues; financing public and private sector transportation improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The other two types of network manager are regional transit agencies, which also provide regional coordination, and completely consolidated regional transit operators. DeRobertis et al found that the flexible nature of the Verkehrsverbund and its coordination-only properties made it well-suited for use in metropolitan regions with quickly growing suburbs, and that the ability of the Verkehrsverbund to coordinate fare policy, planning, schedules, and marketing enabled it to ensure high standards of quality for transit in regions that had one (14).…”
Section: Regional Transit Integration: a Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The other two types of network manager are regional transit agencies, which also provide regional coordination, and completely consolidated regional transit operators. DeRobertis et al found that the flexible nature of the Verkehrsverbund and its coordination-only properties made it well-suited for use in metropolitan regions with quickly growing suburbs, and that the ability of the Verkehrsverbund to coordinate fare policy, planning, schedules, and marketing enabled it to ensure high standards of quality for transit in regions that had one (14).…”
Section: Regional Transit Integration: a Literature Reviewmentioning
confidence: 99%
“…At this point, the RMV basically contained the entire Rhein-Main region. In addition to expanding the area covered by a Verkehrsverbund, the state of Hesse also assigned RMV the power to coordinate all transit within its area (14).…”
Section: Creation Through Bilateral Negotiation Reform By the Statementioning
confidence: 99%